Laringotraqueitis infecciosa aviar en Colombia : características y diagnóstico histopatológico - Morales, Gustavo A.; Aycardi B., Eduardo R.; López, Luis A; González P., Eduardo (1971)
Infectious laryngotracheitis was diagnosed for the first time in Valle del Cauca, Colombia and confirmed by histopathological and virological methods. Descriptions were made of the history of the outbreak, and gross and microscopic lesions produced by the virus